Improving the Ideas Organization in Writing the Recount Text of Junior High School Students Through a Whole Language Approach - I Wayan Karsana; Ni Luh Ketut Mas Indrawati; I Made Rajeg (RIRAI Publisher, 2024)
Language is used as a medium of communication in society. In communicating there are four language skills in the form of listening, speaking, reading, and writing. Language skills are grouped into two, namely assertive skills (listening and reading) and productive skills (speaking and writing). As a productive skill, writing combines the three language skills outlined in the form of writing. Writing skills need to be developed early. Adolescence (14 – 15 years old) is the right time to develop language skills. Writing skills can be developed by starting your own writing experience. Writing experience is included in writing recount text. Ideas are fundamental in writing. The organization of the content of ideas is important because there are ideas that must be developed in it. To develop the organization of the content of students' ideas at junior high school grade eighth SMP Negeri 4 Abiansemal, a whole language approach was applied. The whole language approach includes teaching the four language skills as a whole. Student learning experiences are obtained simultaneously so that they are able to develop themselves from what they like from the language skills taught. The integration of the whole language approach and the ability to teach teachers can increase student scores. Increased grade point average of the class obtained by 4.15 points from 15.71 to 19.86. Keywords: Organization of content ideas, text recount, whole language approach